Sociologia da ciência: estudo bibliométrico da base de dados Scopus - Marcelo, Júlia Fernandes (2012)
The Sociology of Science, presently also known by the Social Studies of Science and Technology, with theoretical and methodological inheritance from the Sociology of Knowledge, debates subjects about the nature of scientific activity and the relationship and interactions between science, technology and society. In this way this research centers on mapping the field of Sociology of Science by its scientific production, as a way to display its trajectory and reflect on its institutionalization as a field of knowledge. The studies about the analysis of scientific production can be included in the field of Sociology of Science and be made ever more frequent. The motivation to investigate this theme is justified by the fact that after the coming of the Internet a variety of different knowledge bases of scientific articles were available online which made much easier the process of data collection and also the treatment of the same. In light of this, the studies of the analysis of scientific production become ever more recurrent. Confronting this reality the research objective of this research was created as to investigate how the field of Sociology of Science configures itself from its scientific production represented by the data base Scopus. The objectives of study were: a) identify and analyze the scientific production on the field of Sociology of Science up from the articles indexed in the database Scopus; b) to understand how the field of Sociology of Science is internationally build, by constructing bibliometric indicators of scientific production like themes in the scope, published journals, authorship, temporal, institutional and geographic distribution of the articles. On the methodological point of view the research is supported on the bibliometric approach and the achieved results shows that a) the field of Sociology of Science follows a parallel growth with the field of Social Studies of Science and Technology; b) the Network Actor Theory is the methodology with the greatest representation in the field, with a growth rate, followed by Ethnographic studies. This exponential growth on the Network Actor Theory is the points to the existence of a trend by other fields in its use; c) around 40% of articles were written in collaboration.